2013
DOI: 10.1021/jm400122f
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2-(2-(1-Naphthoyl)-8-fluoro-3,4-dihydro-1H-pyrido[4,3-b]indol-5(2H)-yl)acetic Acid (Setipiprant/ACT-129968), a Potent, Selective, and Orally Bioavailable Chemoattractant Receptor-Homologous Molecule Expressed on Th2 Cells (CRTH2) Antagonist

Abstract: Herein we describe the discovery of the novel CRTh2 antagonist 2-(2-(1-naphthoyl)-8-fluoro-3,4-dihydro-1H-pyrido[4,3-b]indol-5(2H)-yl)acetic acid 28 (setipiprant/ACT-129968), a clinical development candidate for the treatment of asthma and seasonal allergic rhinitis. A lead optimization program was started based on the discovery of the recently disclosed CRTh2 antagonist 2-(2-benzoyl-3,4-dihydro-1H-pyrido[4,3-b]indol-5(2H)-yl)acetic acid 5. An already favorable and druglike profile could be assessed for lead c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…In vitro models have shown that setipiprant effectively blocks PGD 2 ‐induced activation of eosinophils and basophils, cytokine release by PGD 2 ‐stimulated human Th2‐cells, and eosinophil migration towards PGD 2 . Inhibition of PGD2‐chemotactic eosinophil migration was also demonstrated in a rat model of lung eosinophilia . In a previous phase I study in healthy subjects, setipiprant was well tolerated after single and multiple daily doses up to and including 2000 mg and 1000 mg b.i.d ., respectively .…”
Section: Introductionmentioning
confidence: 80%
“…In vitro models have shown that setipiprant effectively blocks PGD 2 ‐induced activation of eosinophils and basophils, cytokine release by PGD 2 ‐stimulated human Th2‐cells, and eosinophil migration towards PGD 2 . Inhibition of PGD2‐chemotactic eosinophil migration was also demonstrated in a rat model of lung eosinophilia . In a previous phase I study in healthy subjects, setipiprant was well tolerated after single and multiple daily doses up to and including 2000 mg and 1000 mg b.i.d ., respectively .…”
Section: Introductionmentioning
confidence: 80%
“…In Part A, plasma samples were taken predose on Day 1 and 0.5, 1, 1.5, 2, 3, 4, 5, 6, 9, 13, 18, 24, 36 and 48 h after drug intake. In Part B, plasma samples were collected immediately prior to first dose on Day 1, 0.5, 1, 1.5, 2, 3, 4, 5, 6 and 9 h postmorning dose on Day 1, predose starting from Day 1 evening administration up to Day 6 morning administration and 0.5, 1, 1.5, 2, 3, 4, 5, 6,9,12,14,20,24,36 and 48 h postmorning dose on Day 6.…”
Section: Pharmacokinetic Assessmentsmentioning
confidence: 99%
“…To the date of reporting, three CRTH2 antagonists have been tested in phase II trials, i.e. NAV-QAV680, which showed good bioavailability in rats and rodents [87], setipiprant [2-(2-[1-naphthoyl]-8-fluoro-3,4-dihydro-1H-pyrido(4, 3-b)indol-5[2H]-yl)acetic acid] [88], and ARRY-502.…”
Section: Drugs Targeting Crth2 and Crth2/dprmentioning
confidence: 99%